Respuesta :

Answer:

Step-by-step explanation:

Area = length * width

length: x + 3

width: x - 5

A = (x + 3)(x - 5)

Simplify (x + 3)(x - 5) using the FOIL method:

 

1. First numbers: multiply the first number of each binomial together--x*x = x%5E2

2. Outer numbers: multiply the outer number of each binomial (out of the entire expression, the number farthest to the left (x) and the number farthest to the right (-5))--x*-5 = -5x

3. Inner numbers: multiply the inner number of each binomial--3*x = 3x

4. Last numbers: multiply the last number of each binomial--3*-5 = -15

==> Now, add all of the results together and combine like terms: x%5E2+-+5x+%2B+3x+-+15 = x%5E2+-+2x+-+15

Therefore, A = x%5E2+-+2x+-+15

ACCESS MORE